Management compensation and performance: The role of clawback-holdback provisions in mitigating management risk-taking behavior - Septianis, Aulia; Kresnawati, Etik (Journal of Accounting and Investment, 2025)
Research aims: This study aims to examine the mediating effect of management risk-taking behavior on the relationship between compensation of management as a material risk taker (MRT) and bank performance. It also examines how clawback-holdback provisions moderate this relationship. Design/Methodology/Approach: This study employs a quantitative approach, drawing on secondary data from the annual reports of 18 Indonesian banks listed on the Indonesia Stock Exchange (IDX) between 2018-2023. Hypothesis testing was conducted using the mediation moderation model with PROCESS Macro Model 7.Research findings: The results show that management compensation does not directly affect bank performance, but rather indirectly affects it through the risk-taking behavior of MRT. Meanwhile, this study cannot prove the role of clawback-holdback provisions in mitigating the risk-taking behavior of MRT, as expected by the Indonesian Financial Services Authority.Theoretical contribution/ Originality: This study provides evidence that incentive and performance mechanisms in the banking industry are indirect. These results expand our understanding of the importance of behavioral factors, specifically risk-taking by MRT, as a key channel through which incentives translate into performance outcomes. Practitioner/Policy implication: These findings underscore the need for balanced compensation schemes that integrat compensation with risk control. Bank should adopt transparent clawback-holdback provisions aligned with PJOK No.45/PJOK.03/2015.Research limitation/Implication: This study focuses only on banks listed on the IDX, which limits the generalization of its findings to the banking industry as a whole, including private banks and state-owned banks that are not publicly listed. The results of the study highlight the need to enforce clawback-holdback provisions as a mechanism to reduce excessive risk-taking by banking MRTs.